MODEL KINERJA GURU MATEMATIKA SMK KOTA SEMARANG - Suwiyadi, Suwiyadi (Jurnal Penelitian Pendidikan, 2012)
The purpose of this research was to determine the basic model in order to produce a performance increasing mathematics teacher of SMK in Semarang. The population of this research were teachers of mathematics SMK in Semarang by the number of mathematics teachers 249 teachers. The sampling technique using proportional random sampling of 200 teachers. The research was only conducted on a sample group. Samples were partially or representative population research. The data captured by a structured questionnaire scales and analyzed with the AMOS programe. The result of research showed that the data is fit based on the analysis of structural equation modelling, variable on the full model with a significance level (P) against the chi-square for model (104.692) The biggest contribution of each indicator to construct as the following (1) variable of teacherâs work motivation with indicators of self-reliance in the acting of estimate value of 0.840, (2) variable of motivation teacherâs with indicator innovative creative activity estimation value of 0.792, and (3) variable of teacherâs competence with indicator the professional of the estimate value of 0.682. These three variables influensed the performance variables with indicators for the evaluation of the estimate value of 0.755. The implication in this research, self-reliance that is acting teacher in revitalizing teacher forum (MGMP) and create learning with PAIKEM approach, teachers do creative activities that make the planning, implementing and evaluating a coherent and continuous, professional teacher must have mastery of the material, curriculum, and a broad educational foundation.